Sistem Pendukung Keputusan Gizi dan Penentuan Stunting Berbasis Web di Posyandu Mutiara - Rifky Nur Febryan; Arief Ikhwan Wicaksono; Chanief Budi Setiawan; Nurul Fatimah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Posyandu is the activity base in the field of health for the community, with the Posyandu is expected to community conscious will Healt sice early, because of the activities of Posyandu many involving various parties, especially on helath early is a todder. This Posyandu is regulated and supervised by the Puskesmas in order to maximize activities in the field of Healt between RT and RW. In the case of these many activities are still relying on the recording is manually and a lot of data that is not structured. There is also a wighing activity for toddlers who still use the manual method, namely checking the Card Towards Health (KMS) book. The study is intended to create a system supporting decision that can be used by Kader Posyandu in doing the reporting activities of the weighing toddlers and provides a place virtual namely the facility to upload data that is used to store the data Softcopy which can be downloaded back. This system also provides alternative features for determining nutrition and stunting. The result of the study of this form of system support decisions thet help Kader Posyandu in doing the repoting activities of the weighing toddlers and announcements weighing toddlers. The Nutrition Decision Support System and Stunting Determination at the Posyandu Mutiara was designed using the Naïve Bayes Classification method and was made using the PYTHON programming language by utilizing the Flask Framework, Bootstrap Framework, and MySQL as a database.